menu
bartleby
search
close search
Hit Return to see all results

2.3 - Can you show the steps to solving this problem?Differentiate.(33) y = (t^3 + 3t)/(t^2 - 4t +3)

Question

2.3 - Can you show the steps to solving this problem?

Differentiate.

(33) y = (t^3 + 3t)/(t^2 - 4t +3)

check_circleAnswer
Step 1

Please see the white board for the quotient rule of differentiation. In this case f(x) = f(t) =  t3 + 3t and g(x) = g(t) = t2 - 4t + 3

(x)f"(x) -- f(x)9'(x)
g(x)2
f(x)
y =
g(x)
help_outline

Image Transcriptionclose

(x)f"(x) -- f(x)9'(x) g(x)2 f(x) y = g(x)

fullscreen
Step 2

Hence, f'(t) = 3t2 + 3 and g'(t) = 2t - 4

Please see t...

gf()-()g' (t) _ (2- 4t +3)(32+3)- (83) (2t-4)
(t2- 4t3(3t2+3) - (t3t)(2t - 4)
(t2 - 4t 3)
y
g(t)2
_
help_outline

Image Transcriptionclose

gf()-()g' (t) _ (2- 4t +3)(32+3)- (83) (2t-4) (t2- 4t3(3t2+3) - (t3t)(2t - 4) (t2 - 4t 3) y g(t)2 _

fullscreen

Want to see the full answer?

See Solution

Check out a sample Q&A here.

Want to see this answer and more?

Our solutions are written by experts, many with advanced degrees, and available 24/7

See Solution
Tagged in

Math

Calculus

Derivative

Sorry about that. What wasn’t helpful?